Risk of Readmission after Discharge from Skilled Nursing Facilities Following Heart Failure Hospitalization: A Retrospective Cohort Study - Weerahandi, Himali (J Am Med Dir Assoc, 2019)
OBJECTIVE: Discharge to skilled nursing facilities (SNF) is common in patients with heart failure (HF). It is unknown whether the transition from SNF to home is risky for these patients. Our objective was to study outcomes for the 30 days after discharge from SNF to home among Medicare patients hospitalized with HF who had subsequent SNF stays of 30 days or less. DESIGN: Retrospective cohort study. SETTING AND PARTICIPANTS: All Medicare fee-for-service beneficiaries 65 and older admitted 2012 to 2015 with a HF diagnosis discharged to SNF then subsequently discharged home. MEASURES: Patients were followed for 30 days following SNF discharge. We categorized patients by SNF length of stay: 1-6 days, 7-13 days, 14-30 days. For each group, we modeled time to a composite outcome of unplanned readmission or death after SNF discharge. Our model examined 0-2 days and 3-30 days post-SNF discharge. RESULTS: Our study included 67,585 HF hospitalizations discharged to SNF and subsequently discharged home. Overall, 16,333 (24.2%) SNF discharges to home were readmitted within 30 days of SNF discharge. The hazard rate of the composite outcome for each group was significantly increased on days 0-2 after SNF discharge compared to days 3-30, as reflected in their hazard rate ratios: for patients with SNF length of stay 1-6 days, 4.60 (4.23-5.00), SNF length of stay 7-13 days, 2.61 (2.45-2.78), SNF length of stay 14-30 days, 1.70 (1.62-1.78). CONCLUSIONS/IMPLICATIONS: The hazard rate of readmission after SNF discharge following HF hospitalization is highest during the first 2 days home. This risk attenuated with longer SNF length of stay. Interventions to improve post-discharge outcomes have primarily focused on hospital discharge. This evidence suggests that interventions to reduce readmissions may be more effective if they also incorporate the SNF-to-home transition.